The physical capability of community-based men and women from a British cohort: the European Prospective Investigation into Cancer (EPIC)-Norfolk study - Keevil, Victoria L (BioMed Central, 2013)
BACKGROUND: The European Working Group for Sarcopenia in Older People (EWGSOP) published a case-finding algorithm for sarcopenia, recommending muscle mass measurement in older adults with low grip strength (women <20 kg; men <30 kg) or slow walking speed (≤0.8 m/s). However, the implications of adopting this algorithm into clinical practice are unclear. Therefore, we aimed to explore the physical capability of men and women from a British population-based cohort study. METHODS: In the European Prospective Investigation into Cancer-Norfolk study, 8,623 community-based adults (48-92 years old) underwent assessment of grip strength, walking speed, timed chair stands and standing balance. The proportion of older men and women (≥65 years) fulfilling EWGSOP criteria for muscle mass measurement was estimated. Additionally, cross-sectional associations of physical capability with age and sex were explored using linear and logistic regression. RESULTS: Approximately 1 in 4 older participants (28.8%) fulfilled criteria for muscle mass measurement with a greater proportion of women than men falling below threshold criteria (33.6% versus 23.6%). Even after adjustment for anthropometry, women were 12.4 kg (95% Confidence Interval [CI] 12.0, 12.7) weaker, took 12.0% (95% CI 10.0, 14.0) longer to perform five chair stands and were 1.82 (95% CI 1.48, 2.23) times more likely to be unable to hold a tandem stand for 10 seconds than men, although usual walking speed was similar. Physical capability was inversely associated with age and per year, walking speed decreased by 0.01 m/s (95% CI 0.01, 0.01) and grip strength decreased by 0.49 kg (men; 95% CI 0.46, 0.51) and 0.25 kg (women; 95% CI 0.23, 0.27). Despite this, there was still variation within age-groups and not all older people had low physical capability. CONCLUSIONS: Every effort to optimise functional health in later life should be made since poor function is not inevitable. However, if the EWGSOP sarcopenia case-finding algorithm is endorsed, large proportions of older people could qualify for muscle mass measurement which is not commonly available. Considering population ageing, further discussion is needed over the utility of muscle mass measurement in clinical practice.